The Efficacy of Guanxinning Injection in Treating Angina Pectoris: Systematic Review and Meta-Analysis of Randomized Controlled Trials - Jia, Yongliang (Hindawi Publishing Corporation, 2013)
Objective. The randomized controlled trials (RCTs) on Guanxinning injection (GXN) in treating angina pectoris were published only in Chinese and have not been systematically reviewed. This study aims to provide a PRISMA-compliant and internationally accessible systematic review to evaluate the efficacy of GXN in treating angina pectoris. Methods. The RCTs were included according to prespecified eligibility criteria. Meta-analysis was performed to evaluate the symptomatic (SYMPTOMS) and electrocardiographic (ECG) improvements after treatment. Odds ratios (ORs) were used to measure effect sizes. Subgroup analysis, sensitivity analysis, and metaregression were conducted to evaluate the robustness of the results. Results. Sixty-five RCTs published between 2002 and 2012 with 6064 participants were included. Overall ORs comparing GXN with other drugs were 3.32 (95% CI: [2.72, 4.04]) in SYMPTOMS and 2.59 (95% CI: [2.14, 3.15]) in ECG. Subgroup analysis, sensitivity analysis, and metaregression found no statistically significant dependence of overall ORs upon specific study characteristics. Conclusion. This meta-analysis of eligible RCTs provides evidence that GXN is effective in treating angina pectoris. This evidence warrants further RCTs of higher quality, longer follow-up periods, larger sample sizes, and multicentres/multicountries for more extensive subgroup, sensitivity, and metaregression analyses.